Desenvolvimento de um método para inibição de incrustação em tubulação de água do mar utilizando ondas ultrassônicas. - Nascimento, Bruno Maciel do (2019)
The growth and reproduction of living organisms on artificial surfaces is known as biofouling. This is a serious problem in underwater structures such as cables, boat hulls and pipelines of turbine cooling systems from thermoelectric power plants (TPP). An adverse effect on TPP pipelines is the rising resistance to the flow of cooling water, gradually increasing the resistance to heat exchange in the condenser tubes and changing the hydrodynamics of the initial design, causing increasing of operating temperature. In this work, a strategy to inhibit the fixation of organisms on the metallic surfaces in contact with the seawater was investigated. A prototype, based on a condenser of a TPP, allow the circulation of sea water and the creation of an environment favorable to the proliferation of barnacles was developed. The prototype was made from carbon steel tubes and plates, coated with special paints to prevent severe corrosive attacks, and was installed in a location near the sea. A submerged type centrifugal pump was used to feed the prototype with a flow rate of about 1.5 m3/h, returning this flow to the sea. Plates infested with barnacle larvae were used to promote the proliferation of fouling organisms. Commercial transducers of 37 kHz and 50 W were used to promote a unique fouling inhibition mechanism in control plates attached to a transducer or not, and the efficiency of this unique inhibition mechanism reached 91%, comparing the areas embedded by the marine organisms before and after the performance of these transducers. In addition to the effect on the plates, the inhibitory effect of the ultrasound on the mirror of the exchanger near the plate and also on the walls of the prototype, inhibiting the growth in the place, proving to be an innovative and high efficiency mechanism of biofouling inhibition.